Individual cognitive behavioral therapy and combined family/individual therapy for young adults with Anorexia nervosa: A randomized controlled trial. (16th November 2020) - Nyman-Carlsson, Erika; Norring, Claes; Engström, Ingemar; Gustafsson, Sanna Aila; Lindberg, Karolin; Paulson-Karlsson, Gunilla; Nevonen, Lauri
Abstract: Objective: In this study, we evaluate the efficacy of outpatient individual cognitive behavioral therapy for young adults (CBT-YA) and combined family/individual therapy for young adults (FT-YA) for anorexia nervosa (AN). Method: Participants (aged 17–24 years) with AN in Sweden were recruited and assigned to 18 months of CBT-YA or FT-YA. Treatment efficacy was assessed primarily using BMI, presence of diagnosis, and degree of eating-related psychopathology at post-treatment and follow-up. Secondary outcomes included depression and general psychological psychopathology. The trial was registered at http://www.isrctn.com/, ISRCTN (25181390). Results: Seventy-eight participants were randomized, and seventy-four of them received allocated treatment and provided complete data. Clinical outcomes from within groups resulted in significant improvements for both groups. BMI increased from baseline (CBT-YA 16.49; FT-YA 16.54) to post-treatment (CBT-YA 19.61; FT-YA 19.33) with high effect sizes. The rate of weight restoration was 64.9% in the CBT-YA group and 83.8% in the FT-YA group. The rate of recovery was 76% in both groups at post-treatment, and at follow-up, 89% and 81% had recovered in the CBT-YA and FT-YA groups respectively. Conclusions: Outpatient CBT-YA and FT-YA appear to be of benefit to young adults with AN in terms of weight restoration and reduced eating disorder and general psychopathology.